Baricitinib 2 mg for the treatment of atopic dermatitis in North America: Long‐term efficacy and patient‐reported outcomes. Issue 12 (4th November 2022) - Simpson, Eric; Armstrong, April; Boguniewicz, Mark; Chiesa Fuxench, Zelma C.; Feely, Meghan; Pierce, Evangeline; Sun, Luna; Chen, Yun‐Fei; Angle, Robinette; Silverberg, Jonathan I.
Abstract: To address the need for long‐term efficacy and patient‐reported outcomes (PROs) data for patients with atopic dermatitis (AD) treated with baricitinib 2 mg, a study was conducted to evaluate the efficacy of baricitinib 2 mg in adult patients with moderate‐to‐severe AD. Data presented here provided efficacy and outcomes data for patients treated for 52 weeks. Patients who participated in the originating study, BREEZE‐AD5 (NCT03435081), and met additional eligibility criteria could enroll in the multicenter, open‐label, Phase 3, long‐term extension study BREEZE‐AD6 (NCT03559270). Patients received baricitinib 2 mg for the duration of BREEZE‐AD6. In BREEZE‐AD6, the proportion of patients who achieved a 75% improvement in the Eczema Area and Severity Index (EASI75) and validated Investigator Global Assessment for AD (vIGA‐AD™) of 0 (clear) or 1 (almost clear) were assessed through 52 weeks, in addition to several PROs. At week 52, the proportion of patients treated with baricitinib 2 mg daily achieving EASI75 was 48.6% (70/144), and 31.3% (45/144) of patients achieved a vIGA‐AD score of 0 or 1 (clear or almost clear). Improvements in PROs such as SCORing Atopic Dermatitis (SCORAD, itch and sleep) scores, Dermatology Life Quality Index (DLQI) total score, and DLQI ≤5 response were observed, and these responses were sustained through 52 weeks. Long‐term efficacy of baricitinib in patients with AD was demonstrated by both clinician and patient‐reported outcome measures.